Existence Results for Second-Order Impulsive Neutral Functional Differential Equations with Nonlocal Conditions - Meili Li; Chunhai Kou (Discrete Dynamics in Nature and Society)
The existence of mild solutions for second-order impulsive semilinear neutral functional differential equations with nonlocal conditions in Banach spaces is investigated. The results are obtained by using fractional power of operators and Sadovskii's fixed point theorem.